2004
DOI: 10.1002/ijc.20450
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p270 (ARID1A), a component of human SWI/SNF complexes, in human tumors

Abstract: Human SWI/SNF complexes use the energy of ATP hydrolysis to remodel chromosomes and alter gene expression patterns. The activity of the complexes generally promotes tissue-specific gene expression and restricts cell proliferation. The ATPase that drives the complexes, BRG1, is essential for tumor suppression in mice and deficient in a variety of established human tumor cell lines. The complex contains at least 7 other core components, one of which is a large subunit designated p270. p270 RNA is expressed in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
67
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 27 publications
2
67
0
1
Order By: Relevance
“…ARID1A is located in 1p36.11 (Kozmik et al, 2001), a region frequently deleted in human cancers (Huang et al, 2007), and may be involved in cancer development. BAF250A is lost in two cell lines, C33a and T47D , and may be deficient in as many as 30% of renal carcinomas and 10% of breast carcinomas (Wang et al, 2004a). ARID1A-and ARID1B-containing SWI/SNF complexes appear to have antagonistic effects on cell cycle progression, with ARID1A participating in repression and ARID1B in the induction of key cell cycle regulators such as c-MYC (Nagl et al, 2006(Nagl et al, , 2007.…”
Section: Swi/snf Subunits and Their Role In Gene Regulation And Cancermentioning
confidence: 99%
“…ARID1A is located in 1p36.11 (Kozmik et al, 2001), a region frequently deleted in human cancers (Huang et al, 2007), and may be involved in cancer development. BAF250A is lost in two cell lines, C33a and T47D , and may be deficient in as many as 30% of renal carcinomas and 10% of breast carcinomas (Wang et al, 2004a). ARID1A-and ARID1B-containing SWI/SNF complexes appear to have antagonistic effects on cell cycle progression, with ARID1A participating in repression and ARID1B in the induction of key cell cycle regulators such as c-MYC (Nagl et al, 2006(Nagl et al, , 2007.…”
Section: Swi/snf Subunits and Their Role In Gene Regulation And Cancermentioning
confidence: 99%
“…ARID1A is one of the most frequently deleted genes across all cancer types (23,24) and knockdown of this gene results in a failure of cell cycle arrest (23,25). This alteration strongly predominates in kidney, breast and lung cancers in humans (13,26). All inactivating mutations of this gene have been found in these cancers, suggesting that ARID1A plays an essential role during cancer development as a tumor suppressor.…”
Section: Snf5/ini1mentioning
confidence: 99%
“…Loss of the ARID1A protein may cause a failure to regulate the H2B assembly, resulting in accumulation of H2B to high levels. Results using siRNA-knockdown approach indicate that ARID1A is required for cell-cycle arrest (26). Ubiquitination of H2B was associated with transcriptional activation (45).…”
mentioning
confidence: 99%
“…Using immunohistochemistry it was demonstrated that ARID1A mutations result in the loss of the protein BRG-associated factor 250a (BAF250a), which is a large subunit of transcriptionregulating Human SWI/SNF complexes and has an important role in the control of cell proliferation and tumor suppression. 7,9,10 Recently, Guan et al 11 found somatic ARID1A mutations in 10/25 uterine endometrioid carcinomas, and could also confirm a strong correlation to loss of BAF250a expression by immunohistochemistry.…”
mentioning
confidence: 88%